Daya Kecambah Benih Rotan Jernang (Daemonorops draco Blume) dengan Perlakuan Perendaman Zat Pengatur Tumbuh Atonik - Johanna Maria Rotinsulu; Reni Rahmawati; Nuwa Nuwa (HUTAN TROPIKA, 2023)
Good germination of rattan jernang (Daemonorops draco Blume) seeds will increase germination power, germination rate, and germination value. However, there are still obstacles to germination, because the jernang rattan seeds have a dormancy period. Soaking in Atonic Growth Regulatory Substances (ZPT) is one method that can be used to break thedormancy period of seeds. This study aims to determine the dose and soaking time on the germination value of jernang rattan seeds (D. draco Blume). The study used four treatments and 3 groups/replications. The treatment in this study was the dose of ZPT Atonik, namely 50 CC/Liter, 80 CC/liter, 120 CC/liter, 150 CC/liter. Grouped by immersion time, 24 hours, 48 ​​hours and 72 hours. The results showed that the best germination percentage of German rattan (D.draco Blume) seeds were treated with ZPT Atonik dose of 120 cc/liter and soaked for 48 hours with a percentage of 100%. The best seed germination rate was at 150CC/liter treatment and 24 hours of soaking time, which was 50%/day. The highest germination value was found in seeds treated with ZPT 120CC/liter and soaking for 48 hours with an average of 0.0036%/ day. The conclusion of this study is that the ZPT Atonik dose of 120 CC/liter and 48 hours of soaking time has an effect on the percentage of germination power and germination value, while the ZPT dose of 150 CC/liter with 24 hours of soaking time increases the germination rate